A Comparison between Clinical and Pathologic Staging in Patients with Bladder Cancer - Gholamreza Pourmand; Alireza Sina; A Seraji; Daryosh Mansoori; Mohamad Taheri Mahmodi; Abdolrasoul Mehrsai (Urology Journal, 2004)
Purpose: To determine the accuracy of clinical staging methods of bladder cancer and TURBT results in estimating the pathologic stage of tumor. Materials and Methods: Thirty two patients who had undergone radical cystectomy were studied in this retrospective survey. The results of bimanual examination, cystoscopy, TURBT pathology report and the tumor contour in CT scan, (size, infiltrative deepness, pelvic lymph nodes involvement and hydronephrosis) were recorded. The type of surgery and pathologic report of cystectomy sample were analyzed as well. Then the results of bimanual examination, tumor size, hydronephrosis and CT scan findings including tumor infiltrative deepness, pelvic lymph adenopathy and TURBT findings were compared to pathologic results of cystectomy sample. Results: Seven patients were females and 25 were males. Their mean age was 62 (range 36 to 80) years. Gross hematuria and irritative urinary symptoms were the most common complaints. The duration between symptom manifestation and patient’s referral was 5 days to 72 months (mean 12 months). Bimanual examination in estimating the extravesical involvement of tumor had a specificity of 82%, sensitivity of 46%, positive predictive value of 70% and negative predictive value of 63%. The size of tumor in determining extravesical involvement had a specificity of 41%, sensitivity of 93%, and positive predictive value of 58% and negative predictive value of 87%. Hydronephrosis was present in 15 patients of whom, 14 (93%) had bladder muscle involvement. CT scan specificity was 70%, and sensitivity was 46% regarding pelvic lymph adenopathy and perivesical fat involvement. In TURBT report no muscle sample was observed in 11 cases, so that the interpretations of results were impossible. The reported grade of tumor was lower than pathologic sample of cystectomy in 4 patients. Conclusion: Clinical staging in invasive bladder cancers has not high accuracy regarding the involvement of bladder surrounding fats and pelvic adenopathies. A tumor sized more than 5 cm could be sensitive in estimating extravesical involvement. Positive predictive value of hydronephrosis is considerable regarding bladder muscle involvement. Tumor understaging by TURBT is happened in high percentage of patients with invasive bladder cancer.